Cellulose nanocrystal based multifunctional nanohybrids. (July 2020) - Lizundia, Erlantz; Puglia, Debora; Nguyen, Thanh-Dinh; Armentano, Ilaria
Graphical abstract: Abstract: Cellulose nanocrystals (CNC) based nanohybrids are emerging as multifunctional materials and alternative to traditional petroleum-based plastics. The growth in academic and industrial interest in this field is highlighted by the increasing number of works published in the last decade. While several reviews have been focused on the synthesis of these materials, little has been done to catalogue the properties and potential applications of CNC based multifunctional nanohybrids. In this review, we establish an up-to-date state-of-the-art in this field, with a special emphasis on processing, functional properties and application area. The review leads to the combination of cellulose nanocrystals with different types of organic or inorganic nanoparticles, in order to study and analyze the important scientific and industrial uses of the multifunctional nanohybrids and open new horizons in materials science. In particular, engineering and biomedical applications are analyzed, including supercapacitors, solar cells and batteries, separation technologies and wastewater treatment, catalytic, sensing, tissue enegineering, wound dressing, drug delivery and cancer therapy. Nanotoxicity aspects and environmental impact are also discussed.